TRADITIONAL CULINARY OF AYAM TALIWANG AS A TOURIST ATTRACTION IN MATARAM CITY - Bawa Mulyono Hadi (LPPM Institut Pendidikan Nusantara Global, 2023)
This study was motivated by an interest in the expansion of culinary tourism in the city of Mataram, which, although having several opportunities, an abundance of raw materials, one-of-a-kind traditional food preparation techniques, and a promising market share, seems to be developing at a very local level. The strategy that has been used in this study is known as descriptive qualitative research. This means that the method utilized emphasizes monitoring data or information until it is deemed adequate to produce an interpretation. Mataram City is a place that offers a wide variety of different things to do, all of which are impacted by the general circumstances that exist in the surrounding region, including astronomy, geography, administration, and social and cultural aspects. According to the findings, the traditional culinary qualities that serve as an attraction for culinary tourism in the city of Mataram mostly result from the absorption of hereditary ancestral culture that originated in Taliwang, located inside Mataram City. The tourist sector in Mataram City might be expanded and improved by using the city's culinary potential, which could be a direct or indirect method. This is connected to the fact that the cuisine of Mataram City may be both a draw factor and a motivator for people from outside the region to become tourists in Mataram City. This is tied to the fact that the cuisine of Mataram City can be both.